(untitled) - Benz, Ernst (London, 1966)
This book deals not so much with classical Buddhism as a system of religious philosophy - or a collection of systems - as wih Buddhism as the most widespread religion of contemporary Asia.
Keywords: Buddhism,Phật giáo; Asia,Châu Á